2006
DOI: 10.3892/or.16.5.1137
|View full text |Cite
|
Sign up to set email alerts
|

Different molecular pathways determining extrahepatic and intrahepatic recurrences of hepatocellular carcinoma

Abstract: Abstract. Recent genome-wide screens have identified genes associated with the metastatic potential of hepatocellular carcinoma (HCC); however, there is little overlap between the identified genes, and interpretations of the results remain controversial. These inconsistencies may be related to differences in the sample populations, use of distinct microarray platforms and algorithms, and the complicated modes of HCC recurrence. We investigated the gene expression profiles of extrahepatic recurrence (EHR) and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…POSTN had the highest positive correlation and tenth highest correlation with SULF1 in the training and validation data sets, respectively. Although the role of POSTN is not well known in HCC, one study has shown that POSTN expression was associated with extrahepatic recurrence of HCC (Iizuka et al, 2006). POSTN is known to interact with multiple cell-surface receptors and pathways to promote cancer cell survival, epithelial-mesenchymal transition (EMT), invasion, and metastasis (Ruan et al, 2009; Hong et al, 2010).…”
Section: Discusssionmentioning
confidence: 99%
“…POSTN had the highest positive correlation and tenth highest correlation with SULF1 in the training and validation data sets, respectively. Although the role of POSTN is not well known in HCC, one study has shown that POSTN expression was associated with extrahepatic recurrence of HCC (Iizuka et al, 2006). POSTN is known to interact with multiple cell-surface receptors and pathways to promote cancer cell survival, epithelial-mesenchymal transition (EMT), invasion, and metastasis (Ruan et al, 2009; Hong et al, 2010).…”
Section: Discusssionmentioning
confidence: 99%
“…Predictive systems that are developed will enable to accurately detect patients at high risk for early IHR, but there might be many problems to solve before these markers can be applied to daily clinical practice (Iizuka et al, 2004). Thus far, there have been few reports on a predictor for EHR after surgery, although several studies have identified several key genes or gene products related to distant metastasis (Schimanski et al, 2006;Iizuka et al, 2006b). It was reported that HCC recurred in distant organs in only 3 (7%) of 42 patients who underwent liver transplantation, a radical curative treatment strategies (Nart et al, 2003).…”
mentioning
confidence: 99%
“…POSTN had the highest positive correlation and tenth highest correlation with SULF1 in the training and validation data sets, respectively. Although the role of POSTN is not well known in HCC, one study has shown that POSTN expression was associated with extrahepatic recurrence of HCC (Iizuka et al,2006). POSTN is known to interact with multiple cell‐surface receptors and pathways to promote cancer cell survival, epithelial‐mesenchymal transition (EMT), invasion, and metastasis (Ruan et al,2009; Hong et al,2010).…”
Section: Discusssionmentioning
confidence: 99%